CORNWALL-NORTON MODEL IN THE STRONG-COUPLING REGIME - Natale, A. A. (American Physical Soc, 1991)
The Cornwall-Norton model is studied in the strong-coupling regime. It is shown that the fermionic self-energy at large momenta behaves as SIGMA(p) approximately (m2/p)ln(p/m). We verify that in the strong-coupling phase the dynamically generated masses of gauge and scalar bosons are of the same order, and the essential features of the model remain intact.